A systematic review of empirical intraverbal research: 2015–2020. (27th July 2021) - Jennings, Adrienne M.; Vladescu, Jason C.; Miguel, Caio F.; Reeve, Kenneth F.; Sidener, Tina M.
Abstract: The impact of Verbal Behavior (Skinner,  1957) on behavior analytic research, although not immediate, has steadily increased. Empirical investigations of verbal operants initially focused on mands and tacts, yet other operants such as intraverbals, echoics, and autoclitics have started to receive more attention. Aguirre et al. (2016) reviewed intraverbal research between 2005 and 2015. The results showed an increase in intraverbal research, with studies mostly focused on direct intraverbal training and emergent behavior. The authors noted the substantial increase in intraverbal studies assessing emergence, suggesting a subsequent brief review would be beneficial. The purpose of the current review was to replicate and extend Aguirre et al. In addition to analyzing publication trends and research emphasis, we also identified and quantified the skill sets of participants, the method and components of training, and additional procedural details. The findings show a continued increase in intraverbal research, with empirical evidence supporting prerequisite skills.